2007
DOI: 10.1021/jf071187h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Prenylated Flavonoids from Propolis Collected in Okinawa, Japan

Abstract: Propolis is a resinous substance collected by honeybees from various plant sources. The composition of propolis depends upon the vegetation at the site of collection. We previously isolated four prenylated flavonoids from propolis collected in Okinawa, Japan. In this study, further fractionation of the extracts of Okinawan propolis resulted in the isolation of a new prenylated flavonoid, prokinawan, and four known compounds. The structure of prokinawan was determined by MS and NMR spectroscopic methods. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 26 publications
0
82
0
4
Order By: Relevance
“…(Fabaceae) possessed good anti-inflammatory activity as well as antioxidant activity by detecting 2,2 0 -azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH), peroxynitrite (ONOO(À)) and total reactive oxygen species (ROS) (Jung et al, 2008). More emerging evidences also demonstrated that the prenylflavonoids had strong radical scavenging properties toward the DPPH radical (Dufall et al, 2003;Jayasinghe et al, 2008;Kumazawa et al, 2007;Lee et al, 2006;Park et al, 2006).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…(Fabaceae) possessed good anti-inflammatory activity as well as antioxidant activity by detecting 2,2 0 -azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH), peroxynitrite (ONOO(À)) and total reactive oxygen species (ROS) (Jung et al, 2008). More emerging evidences also demonstrated that the prenylflavonoids had strong radical scavenging properties toward the DPPH radical (Dufall et al, 2003;Jayasinghe et al, 2008;Kumazawa et al, 2007;Lee et al, 2006;Park et al, 2006).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…To determine the scavenging activity of an EEP sample, 180 μL of diluted ABTS· + solution was added to each well of a clearbottom, 96-well microplate. EEP solution (20 μL, 1 mg/mL) Previously, we reported prenylated flavonoids with potent antioxidant activity from propolis collected in Okinawa, Japan (Kumazawa et al, 2004a;Kumazawa et al, 2007). Some of these flavonoids were also isolated from Taiwanese propolis (Chen et al, 2008), although Okinawan propolis contains higher amounts of prenylated flavonoids than Taiwanese propolis .…”
Section: Introductionmentioning
confidence: 99%
“…Previously we found that the propolis from Okinawa, Japan, contains some prenylflavonoids not seen in other regions such as Europe and Brazil, suggesting that the plant origin of Okinawan propolis is a plant that grows in Okinawa (Figure 2) [7]. To identify the plant origin of Okinawan propolis, we observed the behavior of honeybees as they collected material from plants and caulked it inside the hive.…”
Section: Pacific Propolismentioning
confidence: 99%
“…These Pacific propolis and prenylflavonoids in it had potent antioxidant and antimicrobial activities. [7].…”
Section: -2mentioning
confidence: 99%